Validation of the ABPMpro ambulatory blood pressure monitor in the general population according to AAMI/ESH/ISO Universal Standard (ISO 81060-2:2018). Issue 3 (5th June 2023) - Roth, Bernhard; Bothe, Tomas Lucca; Patzak, Andreas; Pilz, Niklas
Abstract : Objective: The objective of this study is to evaluate the accuracy of the oscillometric upper-arm device ABPMpro (SOMNOmedics) for ambulatory blood pressure measurement in the general population according to the Association for the Advancement of Medical Instrumentation/European Society of Hypertension/International Organization for Standardization (AAMI/ESH/ISO) Universal Standard (ISO 81060-2:2018) at rest and during dynamic exercise. Methods: Subjects were recruited to fulfill the age, sex, blood pressure (BP) and cuff distribution criteria of the AAMI/ESH/ISO standard using the same arm sequential BP measurement method. Three appropriate cuff sizes (18–24, 24–34 and 34–46 cm) of the tested device were used for the arm-varying circumferences. The inflation and deflation measurement modes of the ABPMpro were investigated. Results: For the general validation study, 100 subjects were recruited and 90 were analyzed. For validation criterion (1), the mean ± SD of the differences between ABPMpro and reference BP was 0.7 ± 7.3/–0.7 ± 5.8 mmHg (systolic/diastolic) for inflation and 1.4 ± 7.7/–0.6 ± 6.1 mmHg for deflation measurements. For criterion (2), the SD of the averaged BP differences per subject was 5.98/5.10 mmHg for inflation and 6.46/5.36 mmHg for deflation measurements, thereby passing the threshold. In the ambulatory validation study ( N = 36), the mean difference was -1.2 ± 7.9/ 2.4 ± 6.6 mmHg for inflation and –0.7 ± 7.6/3.1 ± 7.0 mmHg for deflation measurements. Conclusion: The ABPMpro device fulfilled the ISO 81060-2:2018 requirements in the general population and in the ambulatory setting and can therefore be recommended for clinical use.